Pengaruh Penggunaan Lease Management System, Kualitas Sistem, Dan Kualitas Informasi Terhadap Produktivitas Karyawan Pada Digital Procurement, Dengan Corporate Support Sebagai Variabel Moderasi - Abdul Rachman; Arief Wibowo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the effects of Lease Management System (LeMS) Usage, System Quality, and Information Quality on Employee Productivity, with Corporate Support as a moderating variable in a post-merger telecommunications company. The research employs an explanatory quantitative approach using a survey method involving a total of 109 respondents, consisting of internal employees and external partners engaged in lease asset management processes. Data analysis was conducted using PLS-SEM, encompassing evaluation of the outer model (validity and reliability) and the inner model (R-square, f-square, and path testing through bootstrapping). The results indicate that Information Quality has a significant effect on Employee Productivity, whereas LeMS Usage and System Quality do not show significant effects. In addition, Corporate Support is not proven to moderate the relationships between the three independent variables and Employee Productivity. These findings suggest that during the post-merger transition phase, administrative-process productivity is more sensitive to the accuracy, completeness and timeliness of information than to system usage intensity or technical system quality. The practical implications of this study emphasize the importance of strengthening data governance to maintain the quality of information generated by LeMS, which should be supported by hands-on training to enhance user adoption, as well as policy and SOP updates to ensure more consistent utilization of LeMS in administrative processes, thereby improving employee productivity.